Developing English Learning Material for the Hospitality Students - Garda Arif Wicaksono (Journal Corner of Education, Linguistics, and Literature, 2023)
The purpose of the research is to understand the process of LPK ISI (Indonesia Institute of Technology) in developing English materials. This research focuses on hotel and cruise planning and research products. The method used in this research is research and development (Research and Development) by following of research models is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The procedure in this research the researcher analyses to know the students need what they need and want (teaching goals). After finishing the English course, Design the researcher designs as syllabus, lesson plans, English materials and assessments after that continues to the Development stage, the process is implemented in the classroom, which curriculum; after the learning ends, the researcher evaluates to understand to know the efficacious of the curriculum then, continue to revise the curriculum, the curriculum, which revises the newer for the next batch. Result of this research showed the process of developing English learning material on the students at the three batch until the researcher has done designed English material for the next batch and this research show the product of this research is a textbook, the title is English for Hospitality and Cruise Ship Program.